Editorial: books and debates in economics - D'Ippoliti, Carlo (PSL Quarterly Review, 2021)
This editorial note introduces to the current issue of the journal. On occasion of the centenary of the birth of Paolo Sylos Labini, to whom our journal is dedicated, Economia civile has devoted a special issue Moneta e Credito to the continuing topicality of his thought. Among the new initiatives of the Review, we highlight here the call for submissions of extensive book review articles, which we aim will be a further tool to foster the economic debate on our pages. JEL codes: B31, A11, H63